INTENSITAS PENCAHAYAAN ALAMI PADA RUANG PERTEMUAN DI GEDUNG COT, FAKULTAS TEKNIK GOWA, UNIVERSITAS HASANUDDIN - Annajma Nurul Wika; Nurul Jamala (ATRIUM: Jurnal Arsitektur, 2019)
Title: Natural Light Intensity Analysis in the Meeting Room at COT Building, Gowa Engineering Faculty, Hasanuddin University Lighting is an essential factor in supporting out activities. However, excessive brightness can also cause discomfort. This study aims to examine the intensity of natural lighting in the meeting room of the COT building, Faculty of Engineering, Hasanuddin University. This type of research used is quantitative analysis and data collection methods directly using the lux meter measuring instrument, then presented in tabular form. The study's conclusion is that the intensity of natural lighting in the meeting room of the 1st floor, 2nd and 3rd-floor COT buildings, all exceeding 300 lux from the lighting standards. The average significant light intensity outside the building with clear sky conditions in the morning is 29950 lux; daytime is 18360 lux and afternoon is 14550 lux. The average light intensity outside the building with cloudy sky conditions in the morning is 9200 lux, daytime is 8750 lux, and afternoon is 9350 lux. The average significant light intensity outside the building with cloudy sky conditions in the morning is 3250 lux, daytime is 6610 lux, and the afternoon is 5425 lux. The magnitude of the natural light intensity outside the building with any sky conditions significantly affects the natural lighting in the building. The higher the intensity of the sun light outside the building, the higher the illumination that comes to the building.